Comparison of Continuous Fentanyl and Levobupivacaine Epidural Anesthesia for Perioperative Pain Following Laparotomy in Children Aged 6– 12 Years - Bahtiar Ahmad; Kohar Hari Santosa; Arie Utariani; Lucky Andriyanto (Jurnal Sehat Indonesia (JUSINDO), 2026)
Postoperative pain management in pediatric patients is a clinical challenge because uncontrolled pain can trigger systemic inflammatory responses, slow recovery, and increase the risk of postoperative morbidity. Surgical trauma stimulates the release of proinflammatory cytokines such as interleukin-6 (IL-6) and affects hematologic inflammatory parameters, including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). This study aimed to assess differences in the effectiveness of continuous fentanyl administration and epidural levobupivacaine on inflammatory responses and postoperative pain intensity in pediatric patients undergoing laparotomy. This comparative analytical study involved 30 pediatric patients aged 6–12 years who underwent elective laparotomy and were divided into two groups, namely continuous fentanyl (n=15) and epidural levobupivacaine (n=15). The parameters assessed included IL-6, NLR, and PLR levels, as well as pain intensity using the Numerical Rating Scale (NRS), which was measured in the preoperative and postoperative periods. Statistical analysis was conducted to assess differences within and between groups. The baseline characteristics of the subjects were homogeneous (all p>0.05). The median PLR increased from 136.2 (79.5–411.4) to 161.3 (90.6–616.2) (p=0.106), and the median NLR increased from 1.98 (0.98–19.94) to 2.11 (0.80–28.91) (p=0.643), with no significant differences between groups. IL-6 levels increased significantly overall (p=0.018), significantly in the fentanyl group (p=0.028) but not in the levobupivacaine group (p=0.225). NRS scores decreased significantly in both groups (p<0.001), with a greater reduction in the epidural levobupivacaine group in the early postoperative period (ΔNRS −4 vs −3.07±1.10; p=0.030). Both analgesic modalities were effective in reducing postoperative pain. Epidural levobupivacaine provided better early postoperative pain control and showed a more stable inflammatory response profile compared with continuous fentanyl.